Antimicrobial Activity and Analysis of the Essential Oils of Selected Endemic Edible Apiaceae Plants Root from Caspian Hyrcanian Region (North of Iran) - Azadeh Hamedi; Ardalan Pasdaran Lashgari; Arsalan Pasdaran (Tabriz University of Medical Sciences, 2019)
Background: Different endemic species of Apiaceae that widely grow in Hyrcanian region have long been used as spices and herbal remedies. Chemical compositions and bioactivity of many of these plants have not been studied scientifically. The volatile constituents and antimicrobial activity of four edible Apiaceae plants-Elaeosticta glaucescens Boiss, Malabaila secacul (Mill.) Boiss, Caucalis platycarpos L., and Eryngium caucasicum Trautv-roots were investigated. Methods: Gas chromatography/mass spectrometry (GC-MS) and gas chromatography/flame ionization detection (GC-FID) methods were used for chemical investigation. Antimicrobial potential of the volatile compositions of these roots were investigated using the disc diffusion method on four microorganisms including Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Bacillus subtilis. Results: The best minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of these species were revealed for B. subtilis and S. aureus (500 µg/mL for MIC and MBC) followed by E. caucasicum and C. platycarpus, respectively. The main compounds of E. caucasicum root essential oil were hexyl isovalerate (11.0%) and hexyl valerate (10.1%). E. glaucescens root essential oil was mainly composed of 3(10)-caren-4-ol, acetoacetic acid ester (9.8%), octyl isovalerate (8.9%), and octyl acetate (5.7%). In C. platycarpos root, hexyl isovalerate (9.2%) and n-octyl isobutyrate (8.5%) were constituted the major compositions of the essential oil while n-hexyl isobutyrate (8.5%) and hexyl hexanoate (7.8%) were predominant compounds in M. secacul. Conclusion: The essential oils of E. caucasicum and C. platycarpus roots were contained high amount of short chain fatty acid esters (SCFAE) and trans- pinocarvyl acetate. They exhibited moderate antibacterial activity.